Psychological and Spiritual Maturity in Strengthening Early Marriage Family Resilience in Indonesia - Firman Robiansyah; Aulia Kinarfani; Dinda Aulia Rahmania; Baldan Salim; Saskia Azahra (MADINAH, 2026)
This study examines the reality of early marriage in Indonesia and the role of psychological and spiritual maturity in strengthening the resilience of Islamic families. Early marriage is still influenced by economic, educational, cultural, and social factors, which impact relationship vulnerability, financial stress, and instability in family functioning. The study used a qualitative approach through literature review and analysis of various relevant scientific sources. The results of the study indicate that psychological maturity, including emotional stability, self-control, responsibility, and role readiness, serves as a protective mechanism against conflict and relationship disintegration. Meanwhile, spiritual maturity, which includes the appreciation of religious values, the interpretation of marriage as a trust, and an attitude of patience and trust in God, plays a role in strengthening commitment, meaning, and the quality of family relationships. The integration of these two aspects aligns with the concept of rusyd as an indicator of individual readiness to manage married life responsibly. This study also emphasizes the importance of a strengthening model through premarital education and psychoreligious counseling. These findings provide theoretical and practical contributions to the development of family development programs and policies for preventing early marriage that support the readiness of young couples to face relationship dynamics, socioeconomic pressures, and the sustainability of family life in an adaptive and sustainable future.